2008
DOI: 10.1007/s10567-008-0037-9
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Reconceptualization of Social Aggression: Adaptive and Maladaptive Correlates

Abstract: The emergence of a research literature exploring parallels between physical and nonphysical (i.e., social, relational, indirect) forms of aggression has raised many questions about the developmental effects of aggressive behavior on psychological functioning, peer relationships, and social status. Although both forms of aggression have been linked to problematic outcomes in childhood and adolescence, more recent findings have highlighted the importance of considering the possible social rewards conferred by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 166 publications
3
100
3
2
Order By: Relevance
“…Similar to the significant relationship between peer influence and bullying in our study, a robust body of literature has suggested that peers play a role in this process (Duffy & Nesdale, 2009;Espelage & Holt, 2001;Heilbron & Prinstein, 2008;Ojala & Nesdale, 2004). Thus, football players can be encouraged to use their peer influence-enhanced by their potentially elevated social status as center sport participants-to set and enforce the norm that bullying is unacceptable in their schools and communities.…”
Section: Implications For Prevention Programmingsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar to the significant relationship between peer influence and bullying in our study, a robust body of literature has suggested that peers play a role in this process (Duffy & Nesdale, 2009;Espelage & Holt, 2001;Heilbron & Prinstein, 2008;Ojala & Nesdale, 2004). Thus, football players can be encouraged to use their peer influence-enhanced by their potentially elevated social status as center sport participants-to set and enforce the norm that bullying is unacceptable in their schools and communities.…”
Section: Implications For Prevention Programmingsupporting
confidence: 75%
“…Given the focus on peer influence and peer pressure in the developmental literature (Espelage & Holt, 2001;Heilbron & Prinstein, 2008), one might expect friends to be the strongest predictor of bullying. Although peer influence was significantly related to bullying behavior in our model, the perceived beliefs of the most influential male figure were the strongest predictor of bullying behaviors.…”
Section: Impact Of Social Norms On Bullying Behaviorsmentioning
confidence: 99%
“…This term refers to children's descriptions of manipulations in group acceptance through ostracism or character attacks (Card et al, 2008). These behaviors require the involvement of members of the social community (e.g., gossip, social exclusion, ostracism, negative facial expressions; Heilbron & Prinstein, 2008). Indirect aggression differs from social aggression because the perpetrator does not necessary employ other members in the aggressive act (Xie et al, 2005).…”
Section: Conceptual Clarificationmentioning
confidence: 99%
“…These nonphysical aggressive acts have been given various names, such as indirect, social and relational aggression. As research on these forms of aggressive behavior has substantially expanded, theorists have noted the conceptual confusion characterizing work in this area (Heilbron & Prinstein, 2008). Therefore, it may be instructive to begin by clarifying the underlying differences in constructs referred to as social, relational, an indirect aggression.…”
Section: Introductionmentioning
confidence: 99%
“…Often school friends become the source of conflict ended in intimidation or peer victimization [14][15] [16][17] [18] [19]. Ironically, the victims choose to be silent or object when the doer is going to be reported because of their afraid of being threatened.…”
Section: Introduction (Heading 1)mentioning
confidence: 99%